Anatomo-radiologic Correlation of the Mesial Aspect of the Temporal Lobe and its Application to Epilepsy Surgery (International Journal of Medical and Surgical Sciences, 2014)
The study of the mesial aspect has gained importance due to its anatomic complexity and its relationship to the surgical treatment of epilepsy. The aim of this paper is to do an anatomo-radiologic correlation of the morphology and topography of the mesial aspect of the temporal lobe, with its neurosurgical application in the treatment of diseases in the region. Eight (8) adult formalin fixed hemispheres with no pathologic signs were studied. On 4 of them sections within the 3 planes were performed (sagittal, coronal and axial), for radiologic correlation. On the remaining 4, dissection of the mesial region was done, in order to correlate the structures found during surgical approach to the region. Both in the cadaveric hemispheres and in the radiologic images, structures from the mesial region were identified, this included: collateral sulcus, rinal sulcus, parahippocampal gyrus, temporal uncus, hippocampal sulcus, hippocampus with its 3 sectors (head, body and tail), the inferior choroidal point and the collicular point that divides the hippocampus intro 3 sectors (anterior, medium and posterior). With the results obtained, the principal anamoto- radiologic aspects of the approach to the mesial aspect of the temporal lobe were analyzed, comparing them with results of previous reports. The proper knowledge of both morphologic and topographic anatomy of the mesial aspect of the temporal lobe is crucial for both interpreting radiologic studies and a correct surgical approach for surgical treatment of epilepsy.
Keywords: Temporal lobe; Cerebral magnetic resonance; Hippocampus; Epilepsy surgery; Clinical anatomy